Fruit culture growth in Northeast Brazil and its relationship with work - Costa, Bruna Penha; Carvalho, Alysson Oliveira de; Macedo Júnior, Eurides Kuster; Tsutsumi, Cláudio Yuji; Rego, Carlos Augusto Rocha de Moraes; Vilanova da Costa, Neumarcio (Scientia Agraria Paranaensis, 2022)
Fruit growing in Brazil enhances regional development, as it generates income and absorbs local labor. The Brazilian Northeast presents ideal edaphoclimatic conditions for the development of several fruit trees, mainly in irrigated areas. The objective was to analyze the educational level and the relationship between the wages of men and women employed in the fruit sector, in the Northeast region of Brazil. The selected crops were those of coconut, mango and grape, between the years 2001 to 2018; literacy rate and level of education in Brazil and the northeast region, the relationship between male and female genders, percentage of women in formal jobs in the years 2004 to 2015 and average monthly income in Brazil and the Northeast region and male and female genders in the years 2012 to 2015. There was a reduction in the area cultivated with coconut, however there was no increase in the area for mango and grape crops. Regarding the harvested area, the coconut crop showed a larger cultivated area, however, this area has been gradually reduced. In mango and grape crops, no variations were detected in the harvested areas. As for the average production, the grape crop has higher productivity. In the percentage of formal jobs, literacy and level of education of women, both nationally and regionally, there was a linear growth and higher than those of men. It is concluded that between men and women in the Northeast region, the salary difference was R 354.00, even with women with a higher educational level.